Plant and animal endemism in California - Harrison, Susan (Susan Patricia) (University of California Press, 2013)
California is globally renowned for its biological diversity, including its wealth of unique, or endemic, species. Many reasons have been cited to explain this abundance: the complex geology and topography of its landscape, the special powers of its Mediterranean-type climate, and the historic and modern barriers to the wider dispersal of its flora and fauna. Plant and Animal Endemism in California compiles and synthesizes a wealth of data on this singular subject, providing new and updated lists of native species, comparing patterns and causes of both plant and animal endemism,